2020
DOI: 10.1177/0363546520950731
|View full text |Cite
|
Sign up to set email alerts
|

Impact-Related Ground Reaction Forces Are More Strongly Associated With Some Running Injuries Than Others

Abstract: Background: Inconsistent associations have been reported for impact-related ground reaction force variables and running injuries when grouping all injuries together. However, previous work has shown more consistent associations when focusing on specific injuries. Purpose: To compare ground reaction force variables between healthy and injured runners as a group and within specific common injuries. Study Design: Controlled laboratory study. Methods: A total of 125 runners presenting with patellofemoral pain, tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 45 publications
0
85
1
Order By: Relevance
“…While stiffness has been associated with greater overall injury risk in previous work, 22 emerging research suggests that some biomechanical risk factors are only relevant for certain injury locations. 18 Although our results suggest stiffness may not be a major factor in overall injury risk, further research using clinician-confirmed injuries may be warranted to identify tissue-specific associations between stiffness and injuries to specific load-bearing tissues (e.g., patellofemoral joint, tibia).…”
Section: Discussionmentioning
confidence: 68%
“…While stiffness has been associated with greater overall injury risk in previous work, 22 emerging research suggests that some biomechanical risk factors are only relevant for certain injury locations. 18 Although our results suggest stiffness may not be a major factor in overall injury risk, further research using clinician-confirmed injuries may be warranted to identify tissue-specific associations between stiffness and injuries to specific load-bearing tissues (e.g., patellofemoral joint, tibia).…”
Section: Discussionmentioning
confidence: 68%
“…15 Moreover, the risk of RRI rises more sharply when the magnitude of the loading is increased compared with an increase in the amount of steps taken, 16 emphasising the detrimental effect of too high a loading on the musculoskeletal system. Although internal forces contribute most to the experienced loading, 17 18 external ground reaction forces (GRFs) can be used as operational measures as they reflect these internal forces during level running (FzMax: maximal vertical GRF, [17][18][19][20] or because they are directly identified as risk factors of RRI (peak braking force (PBF) 21 22 and vertical instantaneous loading rate (VILR) [23][24][25][26][27] ). These external force measures relate mechanically to a runners' running style (eg, refs 28 29).…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…Overall, we achieved favorable reductions in AVLR in those with knee complaints with a NRFS transition using an instrumented sock. Our results contribute to an evolving body of literature advocating for an injury-specific approach to biomechanical risk factors for injury (Johnson et al, 2020). At follow-up, the participants demonstrated reduced ground stance time during running.…”
Section: Discussionmentioning
confidence: 51%
“…It is well documented that AVLRs are greater in individuals who run with a RFS pattern versus a non-rearfoot strike pattern (NRFS) (Lieberman et al, 2010;Zadpoor and Nikooyan, 2011;Goss and Gross, 2013;Almeida et al, 2015;Goss et al, 2015;Miller et al, 2020;Xu et al, 2020). Of note, AVLRs greater than 70 BW/s have been associated with tibial and metatarsal stress fractures (Zifchock et al, 2006;Zadpoor and Nikooyan, 2011), patellofemoral pain syndrome (Johnson et al, 2020), and plantar fasciitis (Pohl et al, 2009). It is plausible that altering running biomechanics to reduce AVLR, and thereby improving shock attenuation, may be beneficial in the treatment and prevention of injuries (van der Worp et al, 2016).…”
Section: Introductionmentioning
confidence: 99%